Risk factors for the development of bronchiolitis obliterans in children after suffering from adenovirus pneumonia - Yuan, Jiahao; Wei, Mengyue; Chen, Manke; Wang, Ruizhu; Diao, Jialing; Tian, Man; Zhao, Deyu; Chen, Meng (Frontiers in Pediatrics, 2024)
Introduction: Bronchiolitis obliterans (BO) is an irreversible chronic obstructive lung disease in small airways. The aim of this study was to identify the relevant risk factors for the development of BO in children after suffering from adenovirus (ADV) pneumonia.Methods: An observational cohort study that included 112 children suffering from ADV pneumonia in our institution from March 2019 to March 2020 was performed.We divided the children into a BO group and a non-BO group based on whether they did develop BO or not. Univariate analysis and multivariate logistic regression analysis were applied to identify risk factors for the development of BO. The prediction probability model was evaluated by receiver operating characteristic (ROC) curve analysis.Results: Twenty-eight children (25%) did develop BO after suffering from ADV pneumonia, while 84 children did not. Respiratory support (OR 6.772, 95% CI 2.060-22.260, P=0.002), extended length of wheezing days (OR 1.112, 95% CI 1.040-1.189, P=0.002) and higher lactic dehydrogenase (LDH) levels (OR 1.002, 95% CI 1.000-1.003, P=0.012) were independently associated with the development of BO. The predictive value of this prediction probability model was validated by the ROC curve, with an area under the curve of 0.870 (95% CI 0.801-0.939, P<0.001), a standard error of 0.035, a maximum Youden's index of 0.608, a sensitivity of 0.929, and a specificity of 0.679.After suffering an ADV pneumonia, children who have needed respiratory support, had a longer length of wheezing days or had higher LDH levels are more likely to develop BO.